Association between FIB-4, all-cause mortality, cardiovascular mortality, and cardiovascular disease risk among diabetic individuals: NHANES 1999–2008 - Guan, Lihua; Li, Lei; Zou, Yutong; Zhong, Jian; Qiu, Ling (Frontiers in Cardiovascular Medicine, 2023)
Background: Diabetes is prevalent worldwide and is associated with cardiovascular disease (CVD). Furthermore, diabetic populations are vulnerable to liver fibrosis, which increases the risk of CVD. Fibrosis-4 index (FIB-4)—a non-invasive biomarker for liver fibrosis—is crucial in predicting CVD among patients with liver diseases. However, the association between FIB-4, death, and CVD in the US diabetic population has not yet been investigated. Method: We conducted a cross-sectional study using the data from the National Health and Nutrition Examination Survey (NHANES) 1999-2008. The mortality status was obtained from the National Death Index through December 31, 2015. The association between FIB-4, death, and CVD was analyzed using the restricted cubic spline method and Cox proportional hazards models. Results: The participants (N = 3,471) were divided into alive and dead groups, with the dead group exhibiting significantly higher FIB-4 values. Moreover, the risk of all-cause mortality (HR 1.24; 95% CI, 1.17-1.32) and CVD mortality (HR 1.17; 95% CI, 1.04-1.31) increased with each FIB-4 SD increase after adjusting for all covariates. However, except for myocardial infarction, FIB-4 had no significant effect on the incidence of the other three CVD subtypes (congestive heart failure, coronary heart disease, and angina pectoris). In stratified analysis, we found that the effect of FIB-4 on CVD mortality was influenced by age, and FIB-4 is a risk factor for people older than 60 years (HR 1.14; 95% CI, 1.01-1.29). Conclusion: Using data from NHANES 1999-2008, FIB-4 was found to be associated with all-cause and CVD mortality in the diabetic population, and this association was significantly affected by age. However, FIB-4 only affected the incidence of myocardial infarction. Future work should investigate the association between FIB-4 and CVD in the diabetic population.